Neonatal urinary ascites. Issue 7 (July 1985) - Morrell, P; Coulthard, M G; Hey, E N
Abstract : Two neonates with spontaneous rupture of the bladder and an otherwise normal genitourinary tract are described. Conservative management resulted in complete resolution of the lesion in one but the other child died from a coliform septicaemia. Necropsy showed a discrete ischaemic lesion in the fundus of the bladder.